SACCSG HL-2018. Barriers and enablers of a harmonized treatment protocol for childhood and adolescent Hodgkin lymphoma in South Africa. (3rd April 2023) - Geel, Jennifer; Hendricks, Marc; Goga, Yasmin; Neethling, Beverley; Netshituni, Vutshilo; Mathew, Rema; Vermeulen, Johani; van Zyl, Anel; Omar, Fareed; du Plessis, Jan; du Plessis, Liezl; Madzhia, Elelwani; et al.
Abstract: Introduction: Collaborative studies have contributed to improved survival of pediatric Hodgkin lymphoma in well-resourced settings, but few are documented in resource-constrained countries. The South Africa Children's Cancer Study Group initiated harmonization of management protocols in 2015. This article analyzes barriers and enablers of the process. Methods: Clinician-researchers at 11 state-funded pediatric oncology units completed preparatory questionnaires in June 2018. Parameters included infrastructure, access to therapeutic modalities and clinician numbers. A reassessment of 13 sites (two new pediatric oncology unit) in February 2021 ascertained changes in resources and identified challenges to full participation. Questions investigated the presence and quality of diagnostic radiology, availability of surgeons, cytology/pathology options and hematology laboratory facilities. Results: The response rate was 11/11 to survey 1 and 13/13 to survey 2. The anticipated pre-study barriers to participation of pediatric oncology units included time constraints and understaffing. PET-CT was unavailable to two centers. The majority of pediatric oncology units met the minimum criteria to participate. The interim survey confirmed chemotherapy and radiotherapy availability nearly 100% of the time. One site reported improved access to radiotherapy while another reported improved access to PET-CT. Barriers to participation included excessive times to obtain regulatory approvals, time constraints and lack of dedicated research staff. Enablers include the simple management algorithm and communication tools. Conclusion: This study demonstrates that multicenter collaboration and harmonization of management protocols are achievable in a middle-income setting. Minimal funding is required but full participation to run high-quality studies requires more financial investment. Focused funding and increased prioritization of research may address systemic barriers to full participation.